PENGARUH DISIPLIN BELAJAR, LINGKUNGAN BELAJAR DAN VARIASI MENGAJAR GURU TERHADAP PRESTASI BELAJAR - Wahyuningsih, Roy; Marganingsih, Anna (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to determine (1) the influence of learning discipline on economics learning achievement among PGRI Peterongan High School students. (2) The Influence of the Learning Environment on Economics Learning Achievement of PGRI Peterongan High School Students. (3) The Effect of Teacher Teaching Variations on Economics Learning Achievement of PGRI Peterongan High School Students. (4) The Influence of Learning Discipline, Learning Environment and Teacher Teaching Variations on Economics Learning Achievement of PGRI Peterongan High School Students. This research is quantitative research. The population in this study were all PGRI Peterongan High School students, namely 104 students. The sample in this study used a saturated sample, which used the entire number of students at SMA PGRI Peterongan. The results of the research show that: (1) There is a positive but not significant influence of learning discipline on economics learning achievement of PGRI Peterongan High School students. This is shown by the hypothesis test of the learning discipline variable of 0.865, sig 0.389>0.05. (2) There is a negative and insignificant influence of the learning environment on the economics learning achievement of PGRI Peterongan High School students. This is shown by the hypothesis test for the learning environment variable of -0.094, sig 0.270<0.05. (3) There is an influence on teacher teaching variations on economic learning achievement among PGRI Peterpongan High School students. This is shown by the hypothesis test for the teacher teaching variation variable of 0.009, sig 0.924 <0.05.